DIRECT AND INDIRECT SPEECH ACT IN OPRAH WINFREY’S MOTIVATIONAL SPEECH “LIFE ADVICE WILL CHANGE YOUR FUTURE” - Telaumbanua, Anjelina Inmas Emhardil (Universitas Nias Raya, 2024)
This research was designed in descriptive qualitative research. The aims of the research were to find out direct and indirect speech act and the contextual meaning in Oprah Winfrey’s Motivational Speech “Life Advice Will Change Your Future”. In collecting the data, the researcher used content Analysis technique. The researcher used Miles and Huberman theory in analyzing the data. In doing the research, the theory of Finegan is used. Finegan stated that there were two types of speech act, direct and indirect speech act and it can be in the form of representatives, commissives, directives, declarations, expressives and verdictives. The result shows that there were found 30 expression of direct speech act and 26 expression of indirect speech act. Therefore, speech act can be found in many discourses and daily life conversation. The researcher expected that this research will be useful for teacher, students, and the next researcher who are going to do related research.